Технология частотно-резонансной обработки и интерпретации данных ДЗЗ: результаты апробации и перспективы дальнейшего применения при поисках и разведке рудных полезных ископаемых - Левашов, С.П.; Якимчук, Н.А.; Корчагин, И.Н.; Божежа, Д.Н. (Геоінформатика, 2015)
Анализируются результаты экспериментальной апробации и практического применения мобильной прямопоисковой технологии частотно-резонансной обработки и интерпретации (дешифрирования) данных дистанционного зондирования Земли (ДЗЗ) с целью “прямых” поисков полезных ископаемых различного вида на рудных месторождениях и перспективных площадях. Поисковые исследования с ее применением проведены в рудных районах в Республике Казахстан, Украине, Камеруне, Судане и Канаде. Многие обнаруженные аномальные зоны типа “зона золоторудного оруденения” заверены детальными геолого-геофизическими работами и бурением. Показано, что для обнаружения и картирования мелких объектов (рудных жил) необходимо проводить обработку данных ДЗЗ в крупном масштабе — 1 : 2000 и крупнее. На локальном поисковом участке в районе известного рудного поля Klondike Gold Fields материалы обработки и интерпретации данных ДЗЗ сопоставляются с результатами исследований традиционными геофизическими и геохимическими методами. Включение прямопоисковой технологии в традиционный комплекс поисковых геолого-геофизических методов будет способствовать как минимизации финансовых затрат на решение конкретных поисково-разведочных задач, так и существенному сокращению времени на их практическую реализацию. Проаналізовано результати експериментальної апробації та практичного застосування мобільної прямопошуко- вої технології частотно-резонансної обробки та інтерпретації (дешифрування) даних дистанційного зондування Землі (ДЗЗ) з метою “прямих” пошуків корисних копалин різного виду на рудних родовищах і перспективних площах. Пошукові дослідження з її застосуванням проведено в рудних районах у Республіці Казахстан, Україні, Камеруні, Судані та Канаді. Багато виявлених аномальних зон типу “зона золоторудного зруденіння” завірено детальними геолого-геофізичними роботами та бурінням. Показано, що для виявлення та картування невеликих об’єктів (рудних жил) необхідно проводити обробку даних ДЗЗ у великому масштабі — 1 : 2000 та більше. Для локальної пошукової ділянки в районі відомого золоторудного поля Klondike Gold Fields (Канада) матеріали обробки та інтерпретації даних ДЗЗ зіставлено із результатами досліджень традиційними геофізичними і геохімічними методами. Включення прямопошукової мобільної технології у традиційний комплекс пошукових геолого-геофізичних методів сприятиме як мінімізації фінансових витрат на вирішення конкретних пошуково-розвідувальних завдань, так й істотному скороченню часу на їх практичну реалізацію. Ключові слова: прямі пошуки, частотно-резонансна обробка, рудне родовище, супутникові дані, золото, мідь, срібло, цинк, свинець, залізо, геофізичні та геохімічні дослідження. Purpose. The purpose of the article is to analyze the results of experimental testing and practical application of the mobile direct prospecting technology of the remote sensing (RS) data frequency-resonance processing and interpretation (decoding) for “direct” searches of various types minerals on ore deposits and prospective areas. Exploratory studies conducted with its application within ore bearing areas in the Republic of Kazakhstan, Ukraine, Cameroon, Sudan and Canada. Design/methodology/approach. Experiments carried out with the mobile technology of frequency-resonance processing and interpretation of remote sensing data using, which is the “direct” method of minerals and oil and gas exploration and operates within the “substantial” paradigm of geophysical investigations. The technologies and methods developed on the principles of this paradigm are aimed at searching a particular (desired in each case) substance — gold, silver, copper, lead, zinc, uranium, oil, gas, condensate, etc. Findings. The anomalous zones of the “zones of ore (gold-bearing) mineralization” type detected and mapped within the investigated areas and ore deposits. Many of the found anomalous zones of the “zone of gold mineralization” type were certified by the detailed geological and geophysical works and drilling. It is shown that for small objects (lodes) detection and mapping the remote sensing data processing should be carried out in a large scale — 1 : 2000 and larger. At the local prospecting area within the famous Klondike Gold Fields, the materials of remote sensing data processing and interpretation compared with the results of the investigation by conventional geophysical and geochemical methods. Practical value/implications. This direct prospecting technology inclusion in the traditional complex of exploratory geological and geophysical methods will contribute both to minimizing the financial cost for particular exploration problem solving and to reducing significantly the time to implement them.